(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the concept of "Child" is a mental structure, it is illuminated as a quantum of knowledge in different contents and forms, and it is a multifaceted mental-perceptual phenomenon, and there are conceptual, perceptual, visual-cultural and pragmatic aspects of research using various linguistic tools that directly make up the concept. considered. There are two main approaches to the study of the concept of "concept", that is, cognitive and linguistic studies, which are mainly devoted to the simultaneous study and description of the compatibility of language and culture, and linguistic studies, which are focused on the cultural factor in the person in the language, and on the other hand, the lexemes meaning the concept of "child" used in proverbs are divided into semantic groups separated.